Complete genome of the Medicago anthracnose fungus, Colletotrichum destructivum, reveals a mini-chromosome-like region within a core chromosome - Lapalu, Nicolas; Simon, Adeline; Lu, Antoine; Plaumann, Peter-Louis; Amselem, Joëlle; Pigné, Sandrine; Auger, Annie; Koch, Christian; Dallery, Jean Félix; O'connell, Richard J. (Microbial Genomics, 2024)
Colletotrichum destructivum (Cd) is a phytopathogenic fungus causing significant economic losses on forage legume crops (Medicago and Trifolium species) worldwide. To gain insights into the genetic basis of fungal virulence and host specificity, we sequenced the genome of an isolate from Medicago sativa using long-read (PacBio) technology. The resulting genome assembly has a total length of 51.7 Mb and comprises ten core chromosomes and two accessory chromosomes, all of which were sequenced from telomere to telomere. A total of 15, 631 gene models were predicted, including genes encoding potentially pathogenicity-related proteins such as candidate-secreted effectors (484), secondary metabolism key enzymes (110) and carbohydrate-active enzymes (619). Synteny analysis revealed extensive structural rearrangements in the genome of Cd rela-tive to the closely related Brassicaceae pathogen, Colletotrichum higginsianum. In addition, a 1.2 Mb species-specific region was detected within the largest core chromosome of Cd that has all the characteristics of fungal accessory chromosomes (transposon-rich, gene-poor, distinct codon usage), providing evidence for exchange between these two genomic compart-ments. This region was also unique in having undergone extensive intra-chromosomal segmental duplications. Our findings provide insights into the evolution of accessory regions and possible mechanisms for generating genetic diversity in this asexual fungal pathogen.
CRIS-Team Scopus Importer:2024-09-13
Keywords: accessory chromosome; chromosome rearrangements; fungal genomics; M. truncatula; phytopathogenic fungus; SD

Sugar Accumulation in Leaves of Arabidopsis sweet11/sweet12 Double Mutants Enhances Priming of the Salicylic Acid-Mediated Defense Response. - Gebauer, Pierre; Korn, Martin; Engelsdorf, Timo; Sonnewald, Uwe; Koch, Christian; Voll, Lars (Frontiers in Plant Science, 2017)
In compatible interactions, biotrophic microbial phytopathogens rely on the supply of assimilates by the colonized host tissue. It has been found in rice that phloem localized SWEET sucrose transporters can be reprogrammed by bacterial effectors to establish compatibility. We observed that sweet11/sweet12 double mutants, but not single mutants, exhibited increased resistance toward the fungal hemibiotroph Colletotrichum higginsianum (Ch), both in the biotrophic and the necrotrophic colonization phase. We therefore investigated if the phloem localized transporters AtSWEET11 and AtSWEET12 represent additive susceptibility factors in the interaction of Arabidopsis with Ch. AtSWEET12-YFP fusion protein driven by the endogenous promoter strongly accumulated at Ch infection sites and in the vasculature upon challenge with Ch. However, susceptibility of sweet12 single mutants to Ch was comparable to wild type, indicating that the accumulation of AtSWEET12 at Ch infection sites does not play a major role for compatibility. AtSWEET12-YFP reporter protein was not detectable at the plant-pathogen interface, suggesting that AtSWEET12 is not targeted by Ch effectors. AtSWEET11-YFP accumulation in pAtSWEET11:AtSWEET11-YFP plants were similar in Ch infected and mock control leaves. A close inspection of major carbohydrate metabolism in non-infected control plants revealed that soluble sugar and starch content were substantially elevated in sweet11/sweet12 double mutants during the entire diurnal cycle, that diurnal soluble sugar turnover was increased more than twofold in sweet11/sweet12, and that accumulation of free hexoses and sucrose was strongly expedited in double mutant leaves compared to wild type and both single mutants during the course of Ch infection. After 2 days of treatment, free and conjugated SA levels were significantly increased in infected and mock control leaves of sweet11/sweet12 relative to all other genotypes, respectively. Induced genes in mock treated sweet11/sweet12 leaves were highly significantly enriched for several GO terms associated with SA signaling and response compared to mock treated wild-type leaves, indicating sugar-mediated priming of the SA pathway in the double mutant. Infection assays with salicylic acid deficient sweet11/sweet12/sid2 triple mutants demonstrated that reduced susceptibility observed in sweet11/sweet12 was entirely dependent on the SA pathway. We suggest a model how defects in phloem loading of sucrose can influence SA priming and hence, compatibility.

The many questions about mini chromosomes in colletotrichum spp. - Plaumanns, Peter Louis; Koch, Christian (Plants, 2020)
Many fungal pathogens carry accessory regions in their genome, which are not required for vegetative fitness. Often, although not always, these regions occur as relatively small chromosomes in different species. Such mini chromosomes appear to be a typical feature of many filamentous plant pathogens. Since these regions often carry genes coding for effectors or toxin-producing enzymes, they may be directly related to virulence of the respective pathogen. In this review, we outline the situation of small accessory chromosomes in the genus Colletotrichum, which accounts for ecologically important plant diseases. We summarize which species carry accessory chromosomes, their gene content, and chromosomal makeup. We discuss the large variation in size and number even between different isolates of the same species, their potential roles in host range, and possible mechanisms for intra-and interspecies exchange of these interesting genetic elements.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Accessory region; B-chromosome; Dispensable chromosome; Effector; Lineage-specific region; Mini chromosome; Plant pathogens; Virulence chromosome